Resolving equipment failure causes by root cause analysis and theory of inventive problem solving. (February 2014) - Viveros, Pablo; Zio, Enrico; Nikulin, Christopher; Stegmaier, Raúl; Bravo, Gloria
Failure causes of production systems need to be readily identified, for effective recovery solutions. Root cause analysis can be used for this, integrated by a method for identifying coherent and sustainable solutions. In this article, root cause analysis for failure cause identification is coupled with a method of problem solving to guide the search for effective solutions, called theory of inventive problem solving. The integration of these methodologies is implemented and demonstrated on a real case concerning the solution to the potential failure of the equipment used in the torque test performed on truck engines used in high-tonnage mining operation. The incorporation of a key performance indicator analysis allows evaluating realistically the results obtained and determining the success of the solution.